The impact of intergovernmental transfers on local revenue generation in Africa: Evidence from Tanzania - Takaaki Masaki (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
Do intergovernmental transfers reduce revenues collected by local government authorities (LGAs)? There is already a well-established body of literature in public finance, which argues that intergovernmental grants 'crowd out' local revenues. Most existing studies, however, explore the fiscal implications of intergovernmental transfers in high-income countries where sound fiscal systems are taken for granted. In this paper, I explore the impact of intergovernmental transfers on local revenues in sub-Saharan Africa, a region where local fiscal capacity is limited and endogenously determined by financial support from international donors and the central government. I argue that in places where the existing capacity of LGAs to administer tax collection is weak and political costs of enforcing taxation are low - which are perennial features of many rural districts in Africa - intergovernmental transfers facilitate local revenue generation instead of undermining it. Analysing newly available quarterly fiscal data on local revenues in Tanzania, I show that intergovernmental grants improve the mobilization of local revenues, and also that the positive effect of fiscal transfers on local revenue collection is particularly pronounced in rural districts.
Keywords: H29; H41; H71; H79; 330; public finance; intergovernmental grants; crowding out; sub-Saharan Africa; fiscal capacity; tax collection; local revenues; Tanzania